A Special Issue of the International Journal of Food Studies for the 7th International Iseki-FOOD Conference - Jesus Maria Frias Celayeta; Margarida C. Vieira; Paulo J.A. Sobral (International Journal of Food Studies)
The European Association for Integrating Food Science and Engineering Knowledge Into the Food Chain (Iseki-Food) conference is a biannual event that presents an opportunity for a discussion in education, research and engagement in the food science and technology area. The organising committe aims to provide an environment to exchange ideas and experiences, establish bussiness and research relations and create collaborations. On behalf of the Editorial Team we are announcing an special issue of the International Journal of Food Studies (IJFS) that will receive relevant applications from the conference. We are cordially inviting applications to become Editor and manuscript submissions for this Issue. Applications to become a Special Issue Editor are open for Iseki-FOOD associates. Please email your interest and details to the editor.in.chief@iseki-food.net by the 5th of July 2023.